The Influence of Purchasing Orientations, Online Trust and Online Purchase Experience Toward Customers’ Online Purchase Intention - Nasrul Fadhrullah Isa, Imelda Albert Gisip, Sharifah Nurafizah Syed Annuar, Nelson Lajuni (International Journal of Advanced Science and Technology, 2020)
The world of commerce has seen a revolutionary change by the increasing popularity of the Internet in the realm of online shopping. The involvement of the customer in the online purchase decision process has been the centre of focus in the literature for some timesince the organizations and industry are trying to determine the factors that contribute to a positive purchase experience for the customer. This study is undertaken to assess the influences of purchasing orientation, online trust, online purchasing experience to formulate the intention of customers to purchase online. The study population is Malaysian university students from whom the data is gathered through an online questionnaire. The descriptive assessment of data was done through SPSS, and model assessment was carried out through PLS-SEM on the SmartPLS platform. The findings showed that with the exception of brand orientation, all the other independent variables positively influenced the customer purchase intention online. This research is helpful to retailers in the development of business strategies and also the academicians to conduct further research by adding a new variable in the mix for generation and evolution of the concept.